Tindak Kriminal Dalam Teks Monolog Tolong Karya Nano Riantiarno - Lita Fatmawati; Silpiah Silpiah; Indrya Mulyaningsih (Ikaprobsi, 2023)
This study examines the form of criminal acts in the monologue text Please by Nano Riantiarno. The purpose of this study is to describe the forms of criminal acts contained in the monologue text. This research uses qualitative research and descriptive methods with the sociology of literature approach from Alan Swingewood. The source of the data used was obtained from written data, namely the text of the monologue Please by N. Riantiarno with the data in the form of quotations from the text of the monologue. The results of research on the monologue text Please by N. Riantiarno show that there are criminal acts in the form of physical violence, crime of imprisonment, sexual violence, political crime, and psychological violence. Penelitian ini mengkaji bentuk tindak kriminalitas dalam teks monolog Tolong karya Nano Riantiarno. Tujuan dari penelitian ini untuk mendeskripsikan bentuk tindak kriminalitas yang terkandung dalam teks monolog tersebut. Penelitian ini menggunakan jenis penelitian kualitatif dan metode deskriptif dengan pendekatan sosiologi sastra dari Alan Swingewood. Sumber data yang digunakan diperoleh dari data tertulis yaitu teks monolog Tolong karya N. Riantiarno dengan data berupa kutipan-kutipan dari teks monolog tesebut. Hasil penelitian pada teks monolog Tolong karya N. Riantiarno menunjukkan bahwa terdapat tindak kriminalitas berbentuk kekerasan fisik, kejahatan penyekapan, kekerasan seksual, kejahatan politik, dan kekerasan psikologis.